Franck-Condon factors and vibronic patterns of singlet-triplet transitions of 16O3 molecule falling near the dissociation threshold and above. (October 2021) - Egorov, Oleg; Valiev, Rashid R.; Kurten, Theo; Tyuterev, Vladimir
Highlights: The complete list of the Franck-Condon factors of the singlet-triplet transitions of O3 is presented. The simulation based on electronic-vibrational patterns describes well the measured absorbance from literature in the Wulf region. The intensities of the single lines of the electronic-vibrational-rotational transitions are calculated. The theoretical integrated intensities of the most pronounced hot bands are reported for the region of the dicossiation thereshold of O3 . The integrated intensity of the 3 A 2 (000)← X 1 A 1 (000) cold band agrees well with the available experimental value from literature. Abstract: The Franck-Condon factors were calculated for vertical electronic transitions between the ground singlet ( X 1 A 1 ) and 3 A 2, 3 B 2, and 3 B 1 excited triplet states associated with the Wulf band of the ozone molecule (O3 ). The XMCQDPT2 ab initio method including the static and dynamic electronic correlations was used with the aug-cc-pVQZ basis set. Along with the cold bands, a list of the strongest singlet-triplet hot bands falling into the region of the dissociation threshold of O3 is presented. The absorption coefficient simulated for intensities of the electronic-vibrational patterns agrees well with the measured absorbance from literature. In addition, the intensities of the single lines of the electronic-vibrational-rotational transitions were calculated in absolute units for the most pronounced singlet-triplet hot bands located up to the first 3 A 2 (000)← X 1 A 1 (000) cold band inclusively. The integrated intensity of the 3 A 2 (000)← X 1 A 1 (000) band reported in this work agrees well with the available experimental value from literature. Graphical abstract: Image, graphical abstract